O Estado e a escola na construção da identidade política moçambicana - Basílio, Guilherme (2010)
This thesis aims to discuss the role of government and school building of Mozambican identity. Soon after independence, in 1975, Mozambique began a project of national reconstruction, which consisted in the organization of political institutions, including the organization of school and the construction of new Mozambican identity. The state organized school institutions and school education has become one of the main foundations of construction of revolutionary Mozambican identity and facilitated the consolidation of internal relationship between different ethnic groups that compose Mozambican population. The state and school institutions became crucial for the construction of Mozambique founded on equal rights and training for citizenship and for work. In the organization of political institutions and formation of Mozambican citizenship, FRELIMO (the Mozambican Liberation Front) relied on the principle of national unity, promoted by African Nationalism building, thus, the design of Mozambican citizenship based on the principle of the "New Man". The Mozambican citizenship as a real political project appears as the result of resistance and denial towards colonialism; it is the point of departure and arrival of geopolitical, economical and socio-cultural freedom and independence Mozambicans people. During the socio-political changes occurring in the country, Mozambicans revolutionary transfigured into post-revolutionary identity and democratic. This research discusses the construction of Mozambicans citizenship idea, using a qualitative approach based on documentary sources and books that portray the history of state formation, the National Education System (SNE) and the Mozambican political identity. The concept of Mozambican citizenship owned by the founders was withdrawn through interviews given by certain supporters of the process of national reconstruction. Oral evidences collected through interviews were recorded and interpreted, observing the lines of each of the interviewees. These testimonials confirm the ideas of this construction and the importance of the concept of Mozambican citizenship to strengthen national unity